Dream recall and nightmare frequency in patients with sleep disorders: a diary study - Goitom, Alexander; Schredl, Michael (International journal of dream research, 2020)
As sleep and dreaming are closely intertwined, sleep disorders such as insomnia, restless legs syndrome, sleep-related breathing disorders, or narcolepsy are very likely to have an effect on dream recall, dream quality and nightmare frequency. Previous studies based on questionnaire measures have indeed shown such effects, e.g., heightened dream recall in patients with insomnia, or more frequent nightmares in patients with narcolepsy. The present study measured dream recall frequency, nightmare frequency, and emotional tone of dreams using a 7-day sleep/dream diary that was completed by the patients as part of their clinical routine prior to the first consultation in a sleep center. The sample included 256 patients (138 women, 118 men) with a variety of different diagnoses. In about 55% of the patients, the diagnostic procedure also included two nights with polysomnography. The findings indicate that, overall, patients with sleep disorders showed increased dream recall and nightmare frequencies, and more negatively toned dreams in comparison with healthy controls. This would be in line with the continuity hypothesis assuming that these patients might have experienced more stress during the day. The heightened stress levels might aggravate the sleep disorder and/or be a result of the sleep disorder itself. The findings indicate that studying dreaming in patients with sleep disorders can help patients, i.e., identifying and treating nightmare disorders, and help understand the interactions between waking life, physiological variables, and the dreaming process.
Gesehen am 21.10.2020